Causality Test of Budget and Current Account Deficits in Nigeria: Evidence from Toda and Yamamoto Modified Wald Analysis - Benedict, Imimole (Advances in Social Sciences Research Journal, 2017)
Abstract This paper has investigated the direction of causality between budget deficits and current account deficits in Nigeria within a vector autoregressive (VAR) framework. The Modified Wald test procedure of Toda and Yamamoto (1995) for causality analysis was applied to Nigeria’s annual data series for the period 1970-2015. This involves testing each of the series to determine the maximal order of integration (d-max), determining the optimum lag length (K) and conducting the Modified Wald test. The results of the first two revealed the maximal order as 2, and the optimum lag length as 5. The Modified Wald test was then conducted by estimating the VAR models in their levels with a total of (K + d-max) lags. The results revealed a bi – directional relationship between the two deficits. This means that causality between the two deficits flows from both directions – from fiscal deficits to current account deficits, and from current account deficits to fiscal deficits. To address the problem that may result from this kind of relationship, appropriate policy variables for reducing budget deficits such as taxes and government expenditure, should be manipulated in order to reduce current account deficits. In the same vein, relevant policy measures such as export promotion, equilibrium exchange rate, etc. that would reduce current account deficits should be vigorously pursued as these could play vital role in reducing fiscal deficits.